Impact of headache in women with polycystic ovary syndrome - Zabulienë, Lina; Hendrixson, V.; Urbonas, M.; Ilias, I.; Jatužis, D. (Neurologijos seminarai, 2021)
Background. Polycystic ovary syndrome (PCOS) is one of the most frequent endocrine, metabolic, and androgen excess disorders among reproductive age women. Globally, 46% of the adult population suffer from headache in general. PCOS and migraine pathogenesis are closely associated with insulin resistance. Studies on headache in women with PCOS are scarce. The objective of the study was to evaluate the frequency of headache, its association with metabolic parameters, and impact on daily activities in women with PCOS.Materials and methods. 114 women with PCOS (according to the Rotterdam criteria) and 80 age-matched control women with regular menses and no clinical or biochemical hyperandrogenism or polycystic ovaries were enrolled in the study. Data on age, height, weight, and blood pressure were collected, the body mass index (BMI) was calculated. Participants were tested for complete blood count, fasting glucose, fasting insulin, lipid profile, and comprehensive hormone panel. An ad-hoc questionnaire was given to the participants to obtain information on headache.Results. A total of 60.8% of studied women complained of headache attacks. Women with PCOS experienced headache more frequently than control subjects (68.4% vs. 50.0%, p=0.010). Having PCOS increased the odds ratio of headache by 2.17 (CI: 1.20-3.91, p=0.010). Being overweight or obese increased the odds ratio of having headache by 2.5 times for women with PCOS (OR 2.50, CI: 1.11-5.61, p=0.026). 24.6% of women with PCOS compared with 11.2% of control women reported that headache limited their daily housekeeping activities (p=0.020). 31.6% of women with PCOS compared with 18.8% of control women reported that headache had negative impact on their professional life (p=0.046).Conclusion. Women with PCOS (particularly overweight or obese) in Lithuania are often prone to suffer from headaches; the latter affect their professional life and everyday activities.
Keywords: polycystic ovary syndrome; headache